FBS-Derived Exosomes as a Natural Nano-Scale Carrier for Icariin Promote Osteoblast Proliferation - Dong, Ming; Wu, Saixuan; Xu, Huijun; Yu, Xinxin; Wang, Lina; Bai, Hua; Niu, Weidong (Frontiers in Bioengineering and Biotechnology, 2021)
Cariin is a class IV drug of low solubility, permeability, and poor bioavailability. Synthetic nanomaterials have developed rapidly. However, some literatures point out that synthetic nanomaterials such as liposomes, aptamers, metal nanoparticles and nanogels have high toxicity and are affected by the reticuloendothelial system or mononuclear phagocyte system. It is known that exosomes could be used as an ideal clinical drug delivery vehicle to avoid the above-mentioned problems to a certain extent. Studies have shown that drugs can be loaded into exosomes by passive and active loading. We used FBS exosomes to carry Icariin for the first time in this experiment, FBS EXO-ICA more effectively promoted the proliferation of osteoblasts and bone regeneration than Icariin alone. FBS EXO-ICA could become a new nano-scale drug for treating diseases associated with bone loss.